IRON(III) SOLUBILITY AND SPECIATION IN AQUEOUS SOLUTIONS. EXPERIMENTAL STUDY AND MODELLING: PART 1. HEMATITE SOLUBILITY FROM 60 TO 300°C IN NAOH-NACL SOLUTIONS AND THERMODYNAMIC PROPERTIES OF FE(OH)4-(AQ) - Diakonov I.I.; Schott J.; Martin F.; Harrichourry J.C.; Escalier J. (My University, 1999)
The solubility of natural and synthetic hematite (α-Fe2O3) was measured in NaOH–NaCl solutions (0.007 ≤ m(NaOH) ≤ 2.0) between 60 and 300°C at saturated water vapour pressure and under excess oxygen. Solubility constants determined in the present study and by Yishan et al. (1986) at 300°C were combined with the thermodynamic properties of hematite (Hemingway, 1990) and water (SUPCRT92, Johnson et al., 1992) to generate within the framework of the revised Helgeson–Kirkham–Flowers (HKF) model the standard partial molal thermodynamic properties at 25°C and 1 bar, and the revised HKF equations of state parameters of Fe(OH)4−. The extrapolated value for the Gibbs energy of formation for Fe(OH)4− at 25°C is −201.97 kcal/mol. Thermodynamic calculations show that Fe(OH)4− exhibits a chemical behaviour different from that of Ga(OH)4− and Al(OH)4−.